Middle childhood children interaction with home and neighborhood gardens in urban and rural setting - Shamsuddin, Mohd Suhaizan; Said, Ismail (2008)

(untitled)
This study investigated the properties and attributes of home and neighborhood gardens as a place for middle childhood children to play. The home garden is defined as legal proximity territory demarcated by plants and landform in village and in urban terraced- house neighborhood. The neighborhood garden is an expansion territory range of home garden accessible for public to interact with natural elements. The play involves physical and social performances which are triggered by cognitive performances. Perceptual responses of 120 children, aged 6-12, were elicited using survey questionnaire in a village and a terrace house neighborhood. Data analysis involved the differences of children performances between village and urban, and between home and neighborhood garden. Outdoor participation of children in rural is greater than urban that influenced by variety of feature material, outdoor range, and spaces. It means rural children preferred the outdoor more than their urban counterparts. During play, 48% of rural children used both plants and animals as play tool. On the other hand, only 24% of urban children utilized plant as play tool. The result suggests the rural children were exposed a variety of environmental affordances than their urban counterparts. The affordances are categorized into: performatory (60%), 25% exploratory and 15% productive. It means much of the children performances were physical and social as well as manipulating outdoor elements. This study suggests that rural garden affords more functional affordances than urban garden for children’s performances: physical, social, and cognitive. Finally, this study implies that rural outdoor offers more opportunities and independent mobility for children to be physically active and socially interactive.